Sistem Pendingin Paksa Anti Panas Lebih (Over Heating) pada Rem Cakram (Disk Brake) Kendaraan - Joni Dewanto; Andreas Andreas Wijaya (Jurnal Teknik Mesin (Sinta 3), 2010)
Until now, the vehicle brakes are not usually equipped with a special cooling system, so that the release of heat into the air occurs naturally. When used continuously, the brakes can suffer damage as a result of the occurrence of over-heating. This condition is potentially causing a fatal accident. Physically, the over-heating often occurs in type disc brake, because the heat transfer surface is less proportionately, especially for high braking loads. This research aims to develop a brake disc with an active cooling system to prevent overheating. The system is applied to a simulated model of disc brakes empirically. The test was conducted at several levels of constant disc speed and breaking force. The results of this research indicate that at various braking load, the development of disc brakes with an active cooling system in the form of water vapor that is sprayed, can control the brake temperature rise and prevent over-heating.